MID-CRETACEOUS RADIOLARINS FROM THE BALAMBO FORMATION NE-IRAQ - Al-Dulaimi, Salam; Mahdi, Thamer (Iraqi Journal of Science, 2024)
The late Albian-Early Turonian Radiolarians of the Balambo Formation, which were recovered from well Jambur-18 (NE of Iraq) are characterized by their abundance and diversity. They show certain similarities to those from the Tethys and North Atlantic indicating the ongoing opening between the two basins.Microfacies analysis for the Balambo rocks indicates a basinal depositional environment, where radiolarians thrived. The differences in depositional textures of the carbonate facies with presence of mudstone and shale units indicate relative changes in depth within the same environment. This can interpreted to the relative changes of sea-level, which exhibit transgressive and regressive cycles. Radiolarian-rich intervals correlate well with the transgressive cycles and their associated facies. The maximum flooding surfaces of these cycles are correlated with those identified in the Arabian plate. They represent global events causing the thrive of radiolarian in the study area and other parts of the Tethyan realm during Early Cenomanian-Early-Turonian.